Funcionalidade nas ataxias hereditárias: avaliação, marcadores funcionais da independência na marcha e preditores das quedas - Giangiardi, Vivian Farahte (2021)
Introduction: Hereditary ataxias are characterized with a neurological signal known as “ataxia”, which corresponds to a set of primary ataxias which have genetic inheritance (dominant or recessive). The signs and symptoms of these diseases are, in general, characterized by the progressive decline of selective control of posture and voluntary movement, with uncoordinated and inaccurate movements. The prognosis of hereditary ataxias is not favorable from the functional point of view due to the progressive loss of independence in activities of daily living and consequent restriction on participation in the community. The numerous dysfunctions and functional disabilities resulting from these diseases, make the assessment of these patients to be more comprehensive and with appropriate instruments. However, it is uncertain which of the instruments that evaluates functionality are suitable and which disease characteristics of individuals with hereditary ataxias can be considered functional markers for gait independence and predictors for the risk of falls. Objectives: Identify, using the theoretical model of the International Classification of Disability and Health Functionality (ICF), the main and most suitable instruments for the functional evaluation of individuals with hereditary ataxias. In addition, it is intended to determine the functional markers for gait independence and the predictive factors for the risk of any falls and recurrent falls 3 and 6 months of these individuals. Methods: Initially, a systematic review was conducted to identify the functional instruments that are used in patients with hereditary ataxias, verifying the distribution of these instruments according to the domains of the ICF and the extent to which they are in accordance with these domains (chapter 2). Then, the instruments that have measurement properties were determined through a systematic review, conducted in order to find the articles referring to the evaluation of the measurement properties of these instruments and to classify the level of evidence found in addition to the risk of bias. In this way, it is better to determine the instruments that are most suitable for functional application in hereditary ataxias (chapter 3). In addition, a population of people, of both sexes between the ages of 18 and 90, diagnosed with hereditary ataxias living in the community was studied to determine the functional markers that influence walking independence and to identify the functional predictors that influence the risk of falls at 3 and 6 months. To this end, an exploratory study was conducted, divided into two segments, a transversal (chapter 4) and a longitudinal (chapter 5) using a battery of tests and a semi- structured questionnaire. Gait independence was analyzed based on the participants' self-report on how to get around on a daily basis, and falls were assessed using a weekly fall schedule and monthly telephone calls over a 3- and 6-month follow-up. Results: In the first systematic review related to ICF, most of the functionality instruments found in the literature are related to quality of life, and the upper limb function is less targeted by studies in hereditary ataxias. Most instruments were related to ICF body function and activity domains. There is a need for further revisions that seek to analyze the instruments measurement properties already tested. The results of the systematic review of the measurement properties demonstrated that, to date, there are no consistent instruments to be used in the assessment of “independence in activities of daily living”, “gait, mobility and balance” and “quality of life” for individuals with hereditary ataxias. The instruments that assess “upper limb function”, BBT, JT, 9HPT, grip strength and SFNT are the most reliable to be used in this population, especially in recessive ataxias (Friedreich Ataxia and ARSACS). More quality studies are needed to assess the measurement properties of instruments in hereditary ataxias, in more subtypes. Exploratory studies have shown that gait capacity and dexterity were the main markers related to gait independence in individuals with hereditary ataxias. The 6-minute walk test and the Box and Blocks test are the instruments that can be used, respectively, to better assess the progression of gait independence in hereditary ataxias. In addition, the low adaptability in gait speed (assessed by the 10-meter walk test), low mobility (assessed by the Timed Up and Go Test), the low gait capacity (assessed by the 6-minute walk test) and the Cerebellar syndrome (assessed by SARA) were the main predictors of falls at 3 and 6 months, considering any recurrent falls and falls in individuals with hereditary ataxias. These outcome measures should be used to identify individuals at risk of falling. Strategies to incorporate such assessments should be considered for the functional assessment of the progression of hereditary ataxia.